Change in morphological properties and fatty acid composition of ornamental pumpkin seeds (Cucurbita pepo var. ovifera) and their classification by chemometric analysis - Sekerci, Akife Dalda; Karaman, Kevser; Yetisir, Halit; Sagdic, Osman (SPRINGER, 2017)
Ornamental pumpkin is affiliated to Cucurbitaceae family and included within Cucurbita pepo var. ovifera botanical class. They are commonly grown for ornamental uses and known as a group of hard-shelled, colorful, and odd shaped fruits. In this study, some morphological properties of 38 ornamental pumpkin seeds from different cities in Turkey were determined. And also, oil content and fatty acid composition of the seeds were characterized. Oil contents of seeds were determined in the range of 19-41% and palmitic, stearic, oleic and linoleic acids were detected as the major fatty acids in the samples. Linoleic acid had the highest level among the determined fatty acids (similar to 42-66%). Besides, principal component analysis was performed to characterize and classify the pumpkin seeds depending on the fatty acid composition and fruit morphological properties. Two principal components were obtained from the chemometric analysis and they were found to be explanatory of more than 87.02% of the total variability in the data set for fatty acids. In addition, significant correlations were found between some morphological properties and oil content (P < 0.05). This study is the first report on the oil content and fatty acid composition of ornamental pumpkin seeds belonging to the different genotypes.
Keywords: Ornamental pumpkin; Cucurbita pepo var. ovifera; Morphological characteristics; Fatty acids; Linoleic acid; PCA; CHEMICAL-COMPOSITION; AMINO-ACID; OIL; VARIABILITY; COLLECTION; Food Science & Technology